2008
DOI: 10.4161/cc.7.13.6094
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the replication machinery: Replication fork progression in the absence of processive DNA synthesis

Abstract: The precise coordination of the different steps of DNA replication is critical for the maintenance of genome stability. We have probed the mechanisms coupling various components of the replication machinery and their response to polymerase stalling by inhibition of the DNA polymerases in living mammalian cells with aphidicolin. We observed little change in the behaviour of proteins involved in the initiation of DNA replication. In contrast, we detected a marked accumulation of the single stranded DNA binding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 44 publications
7
32
0
Order By: Relevance
“…These data suggest that RPA, although an essential replication factor, is not visibly clustered into replication foci in living cells. In line with our observations, the in vivo localization GFP-RPA32, was previously investigated and also no replication foci of this RPA subunit were observed in living S-phase cells [38,39].…”
Section: Resultssupporting
confidence: 93%
“…These data suggest that RPA, although an essential replication factor, is not visibly clustered into replication foci in living cells. In line with our observations, the in vivo localization GFP-RPA32, was previously investigated and also no replication foci of this RPA subunit were observed in living S-phase cells [38,39].…”
Section: Resultssupporting
confidence: 93%
“…Biochemical evidence points to the existence of large preformed multiprotein replication complexes that contain all activities (Noguchi et al 1983;Tom et al 1996). However, evidence from live-cell microscopy analysis points to short time interactions between the individual components, suggesting highly dynamic complexes (Sporbert et al 2002;Sporbert et al 2005;Schermelleh et al 2007;Gorisch et al 2008). …”
Section: Dna Replication: the Basicsmentioning
confidence: 99%
“…The combination of time-lapse microscopy with fluorescence photobleaching/activation indicated that the processivity of the replication machinery is built on transient interactions of various replication enzymes with a stable core consisting of the processivity factor PCNA (Sporbert et al 2002;Sporbert et al 2005;Schermelleh et al 2007;Gorisch et al 2008). The latter stayed associated with the DNA and upon photobleaching no recovery was measured for periods of over 10 minutes.…”
Section: Cellular Organization Of Replicationmentioning
confidence: 99%
“…In the recent years, time-lapse microscopy has already been presented as a very promising tool in the field of DNA replication. 56,57,156 Developments in this area over the last decade have provided exciting new insights into the dynamics of DNA replication and its regulation. To really take advantage of the technical improvements that allow the observation of living cells and the visualization of the processes taking place in them over periods of up to days, the available biological tools, as well as the computational resources for data analysis, have been challenged to redefine themselves continuously.…”
Section: Epigenetics and Dna Replication Timing In Mammalsmentioning
confidence: 99%